Effect of Epigallocatechin Gallate on Cisplatin-Induced Nephrotoxicity in Rats - Timurkaan, Mustafa; Demir, Mustafa; Gomleksiz, Muhammet Ridvan; Ozercan, Ibrahim Halil; Şahin, Kazım; Dogukan, Ayhan (Aves, 2021)
Objectives: Nephrotoxicity caused by CDDP is attributed to an increase in kidney oxidative stress, which restricts the therapeutic application of CDDP. EGCG is a very strong green tea-derived antioxidant. To investigate the effect of epigallocatechin gallate (EGCG) on cisplatin (CDDP)-induced lipid peroxidation and nephrotoxicity in rats. Methods: Twenty-eight male Wistar rats (8 weeks, 200-215 g) were used in the research and were separated into 4 equal groups: (1) control rats, (2) EGCG (100 mg/kg, daily) control rats, (3) CDDP-injected rats, CDDP group (7 mg/kg, i.p., single dose), and (4) EGCG-treated (100 mg/kg, daily) plus CDDP-injected rats (EGCG + CDDP group). Results: There was a substantial rise in malondialdehyde (MDA) levels in the CDDP-injected rats (P <.05). The EGCG prevented the rise of the MDA (P <.05). In CDDP-injected rats, renal Bax protein expression was substantially higher compared with control rats, and EGCG therapy significantly decreased Bax protein levels (P <.05). In EGCG + CDDPadministered rats, Bcl-2 protein expression was higher than in CDDP-injected rats (P <.05). In the EGCG + CDDP group, the expression of renal heat shock protein 60 (Hsp60) and heat shock protein 70 (HSP70) was significantly lower compared to CDDP-alone injected rats (P <.001). CDDP-induced renal histopathological changes were significantly improved with EGCG. Conclusion: CDDP produces oxidative stress and renal damage. The EGCG that reduces oxidative stress and changes the expression of Bax and Bcl-2 proteins may potentially have a signi.cant role in the prevention of CDDP-induced renal injury.
Keywords: Cisplatin; nephrotoxicity; epigallocatechin gallate; malondialdehyde; Bax/bcl-2; Hsp60-70